2002
DOI: 10.1038/sj.bjc.6600142
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic effects of the thienopyridine SR 25989 in vitro and in vivo in a murine pulmonary metastasis model

Abstract: Neovascularisation is a key step in tumour growth and establishment of distant metastases. We have recently demonstrated that the thienopyridine SR 25989 an enantiomer of the anti-aggregant clopidogrel (Plavix 1 ) lacking anti-aggregant activity, inhibits endothelial cell proliferation in vitro by increasing the expression of endogenous thrombospondin-1, a natural potent inhibitor of angiogenesis. The anti-angiogenic effect of SR 25989 was further assessed in vitro in a quantitative assay of angiogenesis compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…In accordance with this, a previous study has also shown that treatment with the angiogenesis inhibitor thienopyridine SR 25989 reduces the size and number of lung metastases in a similar metastasis model. 25 Our results show that it should be possible to limit the metastatic process to the development of small metastases that might mostly have only minimal clinical consequences for patients.…”
Section: Discussionmentioning
confidence: 91%
“…In accordance with this, a previous study has also shown that treatment with the angiogenesis inhibitor thienopyridine SR 25989 reduces the size and number of lung metastases in a similar metastasis model. 25 Our results show that it should be possible to limit the metastatic process to the development of small metastases that might mostly have only minimal clinical consequences for patients.…”
Section: Discussionmentioning
confidence: 91%
“…In the laboratory, platelet inhibition by aspirin has been demonstrated to reduce agonist stimulated VEGF and TSP‐1 release from the platelet alpha granule suggesting a plausible mechanism by which local angiogenic protein levels might be controlled in the tumor vasculature micro‐environment in aspirin users . In laboratory models, platelet inhibition by aspirin and thienopyridine derivatives has been demonstrated to decrease angiogenesis, further supporting the suppression of platelet activation as a viable mechanism of influencing tumor angiogenesis …”
Section: Introductionmentioning
confidence: 78%
“…16 In laboratory models, platelet inhibition by aspirin and thienopyridine derivatives has been demonstrated to decrease angiogenesis, further supporting the suppression of platelet activation as a viable mechanism of infl uencing tumor angiogenesis. 17 We have previously demonstrated that the selective endocrine receptor modulators tamoxifen and aromatase inhibitors (AIs; anastrozole, letrozole, and exemestane) have diff erential eff ects on serum angiogenic protein levels. 18 In that study, tamoxifen use was associated with an increase in serum VEGF levels; a result consistent with higher platelet derived VEGF levels in tamoxifen users as compared to nonusers.…”
Section: Introductionmentioning
confidence: 99%
“…However, this proposed mechanism is not supported by the finding that bona fide anti-angiogenic drugs often show only moderate anti-tumor activity when used as single agents, despite their effectiveness at inhibiting tumor angiogenesis. Examples of this include non-small cell lung cancer (8) and glioblastomas (9) in human patients, 9L gliosarcoma xenografts treated in scid mice (4), and metastatic melanomas in C57BL/6 mice (10). Thus, other mechanisms for the improved anti-tumor effects of metronomic chemotherapy are likely operative.…”
Section: Introductionmentioning
confidence: 99%